Mechanism of Ru (III) Catalysed Oxidation of o-Hydroxybenzoic Acid by Acidic Solution of Bromamine-B - K.K. Singh, B; Singh, Nirmala; Kumar, Narendra; K. Singh, Ashok; Singh, B.K. (Asian Journal of Chemistry, 2010)
The kinetics of Ru(III) catalysed oxidation of o-hydroxy benzoic acid (o-HBA) by acidic solution of bromamine-B has been studied. The results indicate that order of the reaction with respect to each of bromamine-B, o-HBA, Ru(III) and H+ ion is one. Negligible effect of addition of potassium chloride and benzene sulphonamide was observed. A suitable mechanism in conformity with kinetic data has been proposed.